The gods of evil in ancient Greek myths (selected models) - Abdel Moneim Mathjal , Researcher. Rafid; Hashem Ali, Prof. Dr. Adel (Basra studies journal, 2025)
The first contrast was between light and darkness, winter and summer, these were natural phenomena that attracted humans. The first problem in their lives was the coexistence of good and evil, crime and virtue, and painting and disease. When those elements were personified, the forces of light became the creators of good, spiritual and earthly. While dark forces re-emerged as principles of evil, this did not mean much to the Greeks, who made human life their starting point for thinking. The Greek concept of evil in the supernatural world can best be understood by first looking at demons, in the simple sense; secondly, those creatures connected with the plan of moral punishment; Third, the nature attributed to the gods.